Legal Uncertainty Regarding the Synergy of Tax Authorities and Corruption Court Authorities in Imposing Tax on Assets Proceedings of Corruption that Have Not Been Reported by Corrupt Perpetrators in Annual Tax Returns - Raden Ferdiandra Defry Yusdanial (Syntax Idea)
This study discusses the legal uncertainty that affects the synergy between the Tax Authority and the Corruption Court Authority (Tipikor) in imposing taxes on assets resulting from corruption that have not been reported by the perpetrators in the Annual Tax Return (SPT). The lack of specific regulations governing the imposition of taxes on assets resulting from corruption causes differences in the interpretation and application of the law in the field, confusing law enforcement officers and business actors. In addition, this study identifies various obstacles faced in coordination between the two authorities, including communication problems, information sharing, and differences in objectives. Using a qualitative approach, this study collected data through interviews with legal practitioners and analysis of relevant legal documents. The results of the study indicate that the existing legal uncertainty and coordination constraints hinder efforts to effectively impose taxes on assets resulting from corruption, thereby harming state tax revenues. This study recommends the need to develop clearer regulations and better cooperation mechanisms between the Tax Authority and the Tipikor Court to improve tax compliance and reduce corrupt practices